INITIATING OVSYNCH ON DAY 6 POST ESTRUS ONSET ± POST AI EARLY LUTEAL PHASE GnRH TREATMENT TO IMPROVE OVARIAN AND FERTILITY RESPONSE IN REPEAT BREEDING CROSSBRED CATTLE - AHMED, N; KATHIRESAN, D; AHMED, F A; LALRINTLUANGA, K; MAYENGBAM, P; GALI, J M (The Indian Journal of Animal Reproduction, 2022)
The study was designed to evaluate the success of ovsynch protocol by initiating the protocol on day 6 after estrus onset with an additional GnRH treatment during post insemination early luteal phase in repeat breeder crossbred cattle. Twenty four repeat breeder cattle were allocated into four groups, Gp I, control; Gp II, GnRH treatment on day 6 post estrus onset; Gp III, Ovsynch treatment initiated on day 6 post estrus onset; Gp IV, same as in Gp III with an additional GnRH on day 6 after 2nd GnRH of ovsynch. The conception rate for gp I, II, III and IV was 0.0, 16.7, 50.0 and 50.0%, respectively. In group II and IV, serum progesterone was high (p<0.01) on day 12 post AI in comparison to Gp I and III, respectively. In conclusion, circulating progesterone was better with an additional GnRH subsequent to ovsynch protocol and the use of ovsynch with or without an additional GnRH treatment during post-AI luteal phase can improve fertility response in repeat breeder crossbred cattle.